2020
DOI: 10.1002/hon.2732
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of controlling nutritional status score on the prognosis of patients with diffuse large B‐cell lymphoma

Abstract: The controlling nutritional status (CONUT) score is a nutritional index calculated from serum albumin and total cholesterol levels and lymphocyte counts. Its role in predicting clinical outcomes of diffuse large B-cell lymphoma (DLBCL) has not been evaluated. In this retrospective study, data from 476 patients with DLBCL were analyzed. The cutoff value of the CONUT score was set as 4. CONUT score significantly stratified the overall survival (OS) and the progression-free-survival (PFS) (5-year OS, 49.0% vs 83.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 76 publications
1
49
0
Order By: Relevance
“…Poor nutritional status is correlated with the toxicity of chemotherapy, resulting in treatment reduction or interruption 17 . The present ndings were consistent with previous reports in other hematological malignancies, which showed the signi cant prognostic utility of the CONUT score in adult T-cell leukemia/lymphoma (ATLL) 11 , DLBCL 12,13 , multiple myeloma 14,15 , myelodysplastic syndrome (MDS), and acute myeloid leukemia (AML) 16 . This study is the rst to con rm the prognostic impact of the CONUT score in patients with PTCL.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Poor nutritional status is correlated with the toxicity of chemotherapy, resulting in treatment reduction or interruption 17 . The present ndings were consistent with previous reports in other hematological malignancies, which showed the signi cant prognostic utility of the CONUT score in adult T-cell leukemia/lymphoma (ATLL) 11 , DLBCL 12,13 , multiple myeloma 14,15 , myelodysplastic syndrome (MDS), and acute myeloid leukemia (AML) 16 . This study is the rst to con rm the prognostic impact of the CONUT score in patients with PTCL.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, the optimal cut-off value of the CONUT score using the ROC curve for predicting the OS of PTCL was 5, the AUC was 0.629 (95% CI 0.519-0.740), sensitivity was 50.9%, and speci city was 77.3%. Nagata et al reported the usefulness of the CONUT score in DLBCL; using an ROC curve with a cut-off value of 4, the AUC was 0.71 (95% CI 0.59-0.78), sensitivity was 59.3%, and speci city was 77.8% 12 . Sakurai et al also reported the utility of the CONUT score in MDS and AML; using an ROC curve with a cut-off value of 5, the AUC was 0.71 (95% CI 0.59-0.83), sensitivity was 84.4%, and speci city was 60.9%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nutritional status assessments using GNRI; BMI and serum level of Alb, PNI; serum level of Alb and TLC, and CONUT score; serum level of Alb, TLC and T-chol, are developed to predict tolerability to cancer treatment in the elderly patients with solid tumors 3,4,[15][16][17] . Recently, the CONUT score has been shown to predict prognosis in patients with some hematological malignancies [5][6][7][8] . However, the prognostic value in AML remained to be determined.…”
Section: Discussionmentioning
confidence: 99%